A Review of Nervonic Acid Production in Plants: Prospects for the Genetic Engineering of High Nervonic Acid Cultivars Plants - Liu, Fang; Wang, Pandi; Xiong, Xiaojuan; Zeng, Xinhua; Zhang, Xiaobo; Wu, Gang (Frontiers in Plant Science, 2021)
Nervonic acid (NA) is a very-long-chain monounsaturated fatty acid that plays crucial roles in brain development and has attracted widespread research interest. The markets encouraged the development of a refined, NA-enriched plant oil as feedstocks for the needed further studies of NA biological functions to the end commercial application. Plant seed oils offer a renewable and environmentally friendly source of NA, but their industrial production is presently hindered by various factors. This review focuses on the NA biosynthesis and assembly, NA resources from plants, and the genetic engineering of NA biosynthesis in oil crops, discusses the factors that affect NA production in genetically engineered oil crops, and provides prospects for the application of NA and prospective trends in the engineering of NA. This review emphasizes the progress made towards various NA-related topics and explores the limitations and trends, thereby providing integrated and comprehensive insight into the nature of NA production mechanisms during genetic engineering. Furthermore, this report supports further work involving the manipulation of NA production through transgenic technologies and molecular breeding for the enhancement of crop nutritional quality or creation of plant biochemical factories to produce NA for use in nutraceutical, pharmaceutical, and chemical industries.